THEORETICAL MODELING OF A TWO-PHASED THERMOSYPHON ASSUMING THE LIQUID RESERVATORY - Zanardi, M. A.; Leite, N. G. C. (Revista de Engenharia Térmica, 2007)
A theoretical modeling using the mass, momentum and energy conservation equations, about the intrinsic phenomena in the working of a cylindrical geometry two-phase thermosyphon operating on vertical was performed. The conservation equations were solved in steady-state operation for all the phases of the thermosyphon. Then model also assumed the presence of a liquid reservatory whose valves of the coefficient of heat transfer that determine the operation of functioning in the reservatory, were obtained from the correlation published in literature. The set of conservation equations was solved by using the method of finite volumes. The results achieved were checked with experimental data from literature and also from specific experiments performed in laboratory. In a general view, the theoric results matched reasonably well with those ones from the experiments, and the observed deviation were assumed by a inadequate prevision of the reservatory model used, besides keeping a stable level of the reservatory of liquid.